2019
DOI: 10.1021/acs.jpca.9b06399
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Polymerization in Cold Plasmas of Acetylene with Ar and He

Abstract: The ionic polymerization of acetylene in cold plasmas of C 2 H 2 /He and C 2 H 2 /Ar has been experimentally studied and modeled in radio frequency (rf) discharges with conditions selected to avoid particle formation. Steady-state distributions of positive and negative ions were measured with mass spectrometry. All the measured distributions are dominated by ions with an even number of carbon atoms, reflecting the characteristic polyyne structures typical for the polymerization of acetylene. The distributions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(41 citation statements)
references
References 51 publications
3
35
0
3
Order By: Relevance
“…This is different to the case of dusty plasmas in which apart from the neutral dissociative production of C 2 H, there is a higher probability for the formation of C 2 + H 2 (from C 2 H 2 ) and C 2 H + (from C 2 H) by electron knocking-off and dissociative ionization processes, respectively. Thus, the chemistry of the formation of NPs in C 2 H 2 dusty plasmas presents a nonnegligible ion-neutral contribution (Jiménez-Redondo et al 2019). In addition, anionic polymeryzation routes can be relevant in acetylene plasmas (Deschenaux et al 1999;De Bleecker et al 2006b;Jiménez-Redondo et al 2019) due to the trapping of negative ions in the plasma potential, despite the electron attachment probability being several orders of magnitude lower than those for electron impact dissociation/ ionization.…”
Section: Formation Of Polyacetylenic Chains (C 2n H 2 )mentioning
confidence: 99%
See 1 more Smart Citation
“…This is different to the case of dusty plasmas in which apart from the neutral dissociative production of C 2 H, there is a higher probability for the formation of C 2 + H 2 (from C 2 H 2 ) and C 2 H + (from C 2 H) by electron knocking-off and dissociative ionization processes, respectively. Thus, the chemistry of the formation of NPs in C 2 H 2 dusty plasmas presents a nonnegligible ion-neutral contribution (Jiménez-Redondo et al 2019). In addition, anionic polymeryzation routes can be relevant in acetylene plasmas (Deschenaux et al 1999;De Bleecker et al 2006b;Jiménez-Redondo et al 2019) due to the trapping of negative ions in the plasma potential, despite the electron attachment probability being several orders of magnitude lower than those for electron impact dissociation/ ionization.…”
Section: Formation Of Polyacetylenic Chains (C 2n H 2 )mentioning
confidence: 99%
“…Thus, the chemistry of the formation of NPs in C 2 H 2 dusty plasmas presents a nonnegligible ion-neutral contribution (Jiménez-Redondo et al 2019). In addition, anionic polymeryzation routes can be relevant in acetylene plasmas (Deschenaux et al 1999;De Bleecker et al 2006b;Jiménez-Redondo et al 2019) due to the trapping of negative ions in the plasma potential, despite the electron attachment probability being several orders of magnitude lower than those for electron impact dissociation/ ionization. However, the chemistry involving anions is very unlikely in SGASs, in which it has been shown that the chemistry proceeds predominantly by neutral-neutral interactions (Haberland et al 1991;Martínez et al 2020) .…”
Section: Formation Of Polyacetylenic Chains (C 2n H 2 )mentioning
confidence: 99%
“…This is different to the case of dusty plasmas in which apart from the neutral dissociative production of C 2 H, there is a higher probability for the formation of C 2 H + 2 (from C 2 H 2 ) and C 2 H + (from C 2 H) by electron-knocking off and dissociative ionization processes, respectively. Thus, the chemistry of the formation of nanoparticles in C 2 H 2 dusty plasmas presents a non-negligible ion-neutral contribution (Jimnez-Redondo et al 2019). In addition, anionic polymeryzation routes can also be relevant in acetylene plasmas (Deschenaux et al 1999;De Bleecker et al 2006b;Jimnez-Redondo et al 2019) due to the trapping of negative ions in the plasma potential, despite the electron attachment probability being several orders of magnitude lower than those for the electron impact dissociation/ionization.…”
Section: Composition Of the Dust Analoguesmentioning
confidence: 99%
“…Thus, the chemistry of the formation of nanoparticles in C 2 H 2 dusty plasmas presents a non-negligible ion-neutral contribution (Jimnez-Redondo et al 2019). In addition, anionic polymeryzation routes can also be relevant in acetylene plasmas (Deschenaux et al 1999;De Bleecker et al 2006b;Jimnez-Redondo et al 2019) due to the trapping of negative ions in the plasma potential, despite the electron attachment probability being several orders of magnitude lower than those for the electron impact dissociation/ionization. However, the chemistry involving anions is very unlikely in SGAS, in which it has been shown that the chemistry proceeds predominantly by neutral-neutral interactions (Haberland et al 1991;Martínez et al 2020) .…”
Section: Composition Of the Dust Analoguesmentioning
confidence: 99%
“…An alternative candidate to probe the size dependence of the activated CH/π interaction among acetylene molecules is (acetylene) n + cluster cations. Because of the excess charge, mass spectrometric techniques are applicable to rigorously select the size of ionic clusters. Of course, the excess charge would largely enhance intermolecular interactions of surrounding molecules, and its effect cannot be ignored.…”
Section: Introductionmentioning
confidence: 99%